AROUSED AND MIND-WONDERING: EEG CONNECTIVITY PATTERN OF THE DEFAULT MODE NETWORK DURING FREE VIEWING OF SEXUALLY EXPLICIT VIDEO - Camila Patricia de Soares Comprido (2022)
The DMN can be considered one of the most studied resting-state networks (RSNs). This network comprises principal hubs, the medial prefrontal cortex (mPFC) and the posterior cingulate cortex (PCC) and plays a role in self-referential processing. A previous study assessed functional connectivity modifications in the DMN hubs during passive viewing of long-VSS in erectile dysfunction patients, hypothesizing a possible role played by the DMN in autobiographical memory related to explicit sexual contexts. However, little is known about functional connectivity modifications of EEG power spectra in the DMN and sexually aroused states in terms of power spectra analysis in women. In this study, 10 women with no sexual dysfunctions or history of general medical diseases engaged in the free viewing of a long erotic clip while their EEG was recorded. The erotic stimuli presented was divided in 4 phases that corresponded to sexual interactions presented. 19 electrodes to access DMN activity. DMN power spectra correlations for each phase were more significant for beta power frequency band over central, parietal, and occipital sites. Internal self-related processing associated to DMN activity might be present during sexual aroused states in women. This potential link needs to be further investigated. Keywords: DMN; EEG; sexual arousal; power spectrum; women.